2017
DOI: 10.18632/oncotarget.14907
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin blocks autophagy and activates apoptosis of malignant mesothelioma cell lines and increases the survival of mice intraperitoneally transplanted with a malignant mesothelioma cell line

Abstract: Malignant mesothelioma (MM) is a primary tumor arising from the serous membranes. The resistance of MM patients to conventional therapies, and the poor patients’ survival, encouraged the identification of molecular targets for MM treatment. Curcumin (CUR) is a “multifunctional drug”. We explored the in vitro effects of CUR on cell proliferation, cell cycle regulation, pro-survival signaling pathways, apoptosis, autophagy of human (MM-B1, H-Meso-1, MM-F1), and mouse (#40a) MM cells. In addition, we evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 77 publications
4
62
0
Order By: Relevance
“…Yamauchi et al () employing ACC‐MESO‐1 as a human‐derived mesothelioma cell line, observed that curcumin decreased cell viability and gave rise to autophagy through the increased LC3B‐II expression and autophagosome formation, but not apoptosis. On the other hand, Masuelli et al () recently observed that curcumin activated apoptosis in a range of human (MM‐B1, H‐Meso‐1, and MM‐F1) and mouse (#40a) malignant mesothelioma cell lines, while elevating Bax/Bcl‐2 ratio, p53 expression, caspase 9 activation, ERK1/2 and p38 phosphorylation, c‐Jun expression and phosphorylation, poly(ADP‐ribose)polymerase 1 cleavage, and yet declining nuclear factor‐κB nuclear translocation, p54 JNK, and Akt phosphorylation. Interestingly, curcumin also evoked and subsequently abolished autophagy as presented by changes in p62 expression in this setting.…”
Section: Influence Of Curcumin On Autophagy‐apoptosis Crosstalkmentioning
confidence: 99%
“…Yamauchi et al () employing ACC‐MESO‐1 as a human‐derived mesothelioma cell line, observed that curcumin decreased cell viability and gave rise to autophagy through the increased LC3B‐II expression and autophagosome formation, but not apoptosis. On the other hand, Masuelli et al () recently observed that curcumin activated apoptosis in a range of human (MM‐B1, H‐Meso‐1, and MM‐F1) and mouse (#40a) malignant mesothelioma cell lines, while elevating Bax/Bcl‐2 ratio, p53 expression, caspase 9 activation, ERK1/2 and p38 phosphorylation, c‐Jun expression and phosphorylation, poly(ADP‐ribose)polymerase 1 cleavage, and yet declining nuclear factor‐κB nuclear translocation, p54 JNK, and Akt phosphorylation. Interestingly, curcumin also evoked and subsequently abolished autophagy as presented by changes in p62 expression in this setting.…”
Section: Influence Of Curcumin On Autophagy‐apoptosis Crosstalkmentioning
confidence: 99%
“…Several studies have demonstrated that curcumin is capable of inducing autophagy in different lines of human tumor and normal cells [22,23,[27][28][29]. However, recent studies have revealed that curcumin impairs autophagic flux both in vitro and in vivo [30,31]. The roles of curcumin and its analogs on autophagy regulation remain controversial because in most studies, especially in the earlier studies, the autophagic flux was not carefully examined.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the discussion above, we could deduce that one of the important mechanisms for CBBR to inhibit the proliferating activity of CNE2 cells might be achieved through activating their autophagic response, as that of quercetin to promote hepatoma cells going into apoptotic program via inducing autophagy at first [29]. Meanwhile, curcumin could induce apoptosis in malignant mesothelioma cells through initiating autophagy flow so as to suppress their level of proliferation [30]. Some ingredients of herbal medicine, such as TanshinoneI (TSI) and…”
Section: Discussionmentioning
confidence: 97%